A comprehensive techno-economic analysis of income-generating sources on the conversion of real sheep slaughterhouse waste stream into valorized by-products. (15th March 2022) - Yetilmezsoy, Kaan; Ilhan, Fatih; Kiyan, Emel; Bahramian, Majid
Abstract: The present analysis was conducted as the first research to assess the techno-economic viability of the value-added by-products (struvite, blood meal, bone meal, and raw sheepskin) from a medium-scale sheep slaughterhouse facility with a slaughtering capacity of 300 sheep per day. For this aim, a comparative technical and economic feasibility analysis was performed to assess the synergistic use of slaughterhouse-oriented rendering wastes and struvite recovery from real sheep abattoir effluent within the framework of detailed cost breakdown, break-even point, and payback period analyses. The experimental findings clearly showed that under the optimal conditions (chemical combination of MgCl2 .6H2 O + NaH2 PO4 .2H2 O, a molar ratio of Mg 2+ :NH4 + -N:PO4 3- -P = 1.2:1:1, a reaction pH of 9.0, an initial ammonium concentration of 240 mg NH4 + -N/L, and a reaction time of 15 min), struvite precipitation could effectively remove about 73%, 64%, 59%, and 82% of NH4 + -N, TCOD, SCOD, and color, respectively, from the real sheep slaughterhouse waste stream. Based on various up-to-date techno-economic items considered within the break-even point analysis, the sheep slaughterhouse facility was estimated to achieve the targeted net income (€100/day) for any selling prices of €1041.30/ton, €640.05/ton, €263.72/ton, and €1.012/hide, respectively, for struvite, blood meal, bone meal, and raw sheepskin. Steel construction and chemicals were determined as the most costly components for CAPEX (capital expenditures) and OPEX (operating expenditures), respectively, and selling prices of bone meal and raw sheepskin were found to be the most critical income items on the profitability of the slaughterhouse facility. Co-monetary assessment of the struvite process and valorized compounds corroborated the economic viability of the proposed project with the payback periods of about 6.3 and 5.5 years, respectively, for the current market and the profit-oriented conditions without subsidy. The findings of this feasibility analysis, as the first of its own, could be used as guideline for simplifying the decision-making with regards to the feasibility of similar facilities and commercialization of profitable by-products. Graphical abstract: Image 1 Highlights: Income-generating real sheep slaughterhouse concept is described for the first time. High profit corridor is reached when the sales price of struvite exceeds €1041.30/ton. Daily net profit is predicted as €12.22/kg NH4 + -Nremoved at optimum MAP conditions. Facility can pay for itself less than 6 years for unsubsidized profit-oriented case. Valorized by-products offer an eco-sustainable way for meat processing facilities.